Konseptualisasi Manusia dan Pemimpin dalam Pemilihan Gubernur Jakarta Tahun 2017: : Sebuah Kajian linguistik Kognitif - Aliurridha; Elya Febriani; Mustakim Saleh (Madah: Jurnal Bahasa dan Sastra, 2025)
Abstract Humans and leaders are crucial topics in the 2017 Jakarta Governor Election. Both gubernatorial candidates and their running mates employed distinct metaphors to elucidate these two subjects.  This research aims to explore how humans and leaders were conceptualized in the 2017 Jakarta Governor Election and to evaluate the consistency of these metaphors. This research employs a descriptive qualitative methodology utilizing a cognitive linguistics perspective. Data of this research were collected through reading and note-taking techniques. The data were then analyzed using referential and abductive inferential methods.  The findings of this research revealed that Ahok-Djarot conceptualized humans as buildings, containers, computers, inanimate objects, and broken entities, whereas Anies-Sandi conceptualized humans solely as buildings. In leadership discourse, Ahok-Djarot conceptualized leaders as servants, parental figures, and administrators of justice, whereas Anies-Sandi characterized leaders as role models, brothers to the people, and  courier. The Ahok-Djarot candidate pair demonstrated inconsistencies in employing their metaphor regarding these two topics.